Pengembangan Media Augmenteed Reality Untuk Meningkatkan Hasil Belajar IPA Terpadu Siswa Kelas VIII SMPK Santo Fransiskus Assisi Samaarinda - Petrus Gega; Makrina Tindangen; Sonja V.T Lumowa (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2021)
This development research aims: (1) determine the design of augmented reality media development to improve learning outcomes of integrated science learning outcomes for VIII grade students of SMPK Santo Fransiskus Assisi Samarinda, (2) determine the feasibility of developing augmented reality media on the excretion system (kidney) material of grade VIII students of SMPK Santo Fransiskus Assisi Samarinda, (3) to determine the effectiveness of the development of augmented reality media on the excretion system (kidney) material of grade VIII students of SMPK Santo Fransiskus Assisi Samarinda. This development research refers to the research steps of Dick & Carey's product development design. Product development in this research is designed with the following stages: (a) the analysis stage, (b) the planning and design development stage, (c) the design development and validation stage, (d) the design evaluation and revision stage, (e) the design stage preparation of improvement models, (f) product trial stage, (g) product evaluation and revision phase, (h) experimental trial stage. Product testing consists of alpha testing / validation conducted by material experts and media experts, as well as beta testing which is carried out in 2 stages, namely beta 1 / empirical test (small group trial). Data collection used interview guidelines, observation, questionnaires for material experts, and questionnaires for media experts, student response questionnaires, and test script instruments. This research produces teaching media that is packaged in the form of an application (apk.) which can be used on Android and iPhone. Based on the results of the extensive test, learning media that utilize Augmented Reality technology can improve student learning outcomes in class VIII, from the pre-test data, the experimental and control groups are not much different, so it can be assumed that students from both groups have homogeneous and comparable abilities, namely 57: 58,75 . But after being given the difference in teaching materials and the similarity of teaching in front of the class, the effect was significant, namely 85.1: 78.8. Whereas referring to the independent t test for equality output table in the equal section assumed the sig value is known. (2-tailed) is 0.010 <0.05, so as the basis for making independent t-test decisions it can be concluded that Ho is rejected and Ha is accepted or there are differences in student learning outcomes given Augmented Reality media and not.